To assess environmental damage: the case of the oil spill off the coast of Ventanilla - Loyola, Roger (2023)
This article analyzes the considerations that must be taken into account to measure the environmental damage caused by the oil spill on the coast of Ventanilla, from an economic point of view. To do this, similar cases are reviewed and minimum considerations to be taken into account in this case are established, based on previous studies. The problems found in these contexts seem to be present in the case in question, which makes an analysis necessary if you are considering using this value for a future legal claim.